Targeting Striatal Metabotropic Glutamate Receptor Type 5 in Parkinson’s Disease: Bridging Molecular Studies and Clinical Trials - Vallano, A.; Fernandez-Duenas, V.; Garcia-Negredo, G.; Quijada, M.A.; Simon, C.P.; Cuffí, M.L.; Carbonell, L.; Sanchez, S.; Arnau, J.M.; Ciruela, F. (CNS & Neurological Disorders - Drug Targets, 2013)
Metabotropic glutamate (mGlu) receptors are G protein-coupled receptors expressed primarily on neurons and glial cells modulating the effects of glutamatergic neurotransmission. The pharmacological manipulation of these receptors has been postulated to be valuable in the management of some neurological disorders. Accordingly, the targeting of mGlu5 receptors as a therapeutic approach for Parkinson’s disease (PD) has been proposed, especially to manage the adverse symptoms associated to chronic treatment with classical PD drugs. Thus, the specific pharmacological blocking of mGlu5 receptors constitutes one of the most attractive non-dopaminergic-based strategies for PD management in general and for the L-DOPA-induced diskynesia (LID) in particular. Overall, we provide here an update of the current state of the art of these mGlu5 receptor-based approaches that are under clinical study as agents devoted to alleviate PD symptoms.
Keywords: GPCR oligomerization